In vitro morphogenesis from leaves fragments of pear and apple rootstocks - Silva Camargo, Samila Silva Camargo; Meneguzzi, Aline; Juline Gonçalves, Mayra; Grimaldi, Fernanda; Rufato, Leo (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2019)
The plant tissue culture represents advantages such as the large scale increase in number of individuals, the possibility of maintaining biodiversity from germplasm conservation. The objective was to verify the in vitro morphogenesis of leaves, of the two rootstocks used in apple and pear growing, ‘G 874’ and ‘OHxF 87’, respectively. The study is based on the need of obtaining quality materials from in vitro propagation technique, which enable a greater homogeneity of the plants, in a short period of time and in addition, a possibility of germplasm conservation. For two different cultivars of rootstocks, experiments were performed, a triple factorial with three types of growth regulators - BAP, 2iP and NAA -, five concentration - 0, 4, 8, 12 and 16 mg L-1 - and two leaf cut direction - longitudinally and transversely. Based on the results, it was concluded that the presence of part of the midrib favors the formation of calluses in vitro and for callus induction of cultivars OHxF 87 and G 874 is necessary the presence of 4 mg L-1 and 8 mg L-1 of NAA, respectively. The addition of auxin to the culture medium favors in vitro morphogenesis of leaves, as well as the number of calluses, number of roots and root length of ‘OHxF 87’ and ‘G 874’.